Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1007/bf01644173
|View full text |Cite
|
Sign up to set email alerts
|

Antikörperprävalenz gegen HHV-6 in verschiedenen Altersgruppen, bei Kindern mit Exanthema subitum, anderen akuten exanthematösen Krankheiten des Kindesalters, Kawasaki-Syndrom sowie akuten Infektionen mit anderen Herpesviren und HIV

Abstract: We determined IgG antibodies against Human Herpesvirus-6 (strain Uganda 1102, M. D. Griffin, London) in the indirect immunofluorescence test in sera from 1105 persons of various age groups. Of these sera 570 were retested using HHV-6 strain St. W. (Prof. Schneweis, Bonn). We could confirm that maternal antibodies decrease between birth and six months of age and the seropositive rate rises rapidly between seven months and five years of age up to 79.5%. Between six and ten years and up to 40 years, the antibody-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 13 publications
0
11
0
4
Order By: Relevance
“…Although HHV-6 has been implicated as the causative agent of Exanthem subitum, sero-epidemiological studies using immunofluorescence techniques have identified other disease categories with unusually high antibody titers to this virus Krueger et al, 1988;Saxinger et al, 1988;Levine et al, 1989;Okano et al, 1989;Clark et al, 1990;Enders et al, 1990;Irving and Cunningham, 1990;Steeper et al, 1990;Ablashi et al, 1991;Levine et al, in press). The significance of the high titers to disease association in most cases remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HHV-6 has been implicated as the causative agent of Exanthem subitum, sero-epidemiological studies using immunofluorescence techniques have identified other disease categories with unusually high antibody titers to this virus Krueger et al, 1988;Saxinger et al, 1988;Levine et al, 1989;Okano et al, 1989;Clark et al, 1990;Enders et al, 1990;Irving and Cunningham, 1990;Steeper et al, 1990;Ablashi et al, 1991;Levine et al, in press). The significance of the high titers to disease association in most cases remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Results from sero-epidemiological studies have indicated that initial exposure to this virus occurs at a very young age (Knowles and Gardner, 1988;Okuno et al, 1989;Enders et al, 1990). As with other herpesviruses, the virus remains in the exposed individual for life in a latent state following primary infection.…”
mentioning
confidence: 99%
“…In the USA, UK and Japan, 97–100 % of primary infections by these two viruses are caused by HHV-6B and occur between the ages of 6 and 12 months [43, 51, 125, 130, 134]. Less is known about the epidemiology of HHV-6A infection.…”
Section: Distinct Epidemiology and Disease Associationsmentioning
confidence: 99%
“…HHV-6 is generally acquired between 6 and 15 months of age (120,316), and the incubation period is 1 to 2 weeks. Primary HHV-6 infection accounts for 20% of all cases of acute fever in children between 6 and 12 months old (154) and is almost exclusively caused by HHV-6B, not HHV-6A (101,356).…”
Section: Clinical Features Of Hhv-6 Epidemiologymentioning
confidence: 99%